Analysis of bleeding after ultrasound-guided core needle biopsy of infected cervical lymph nodes - Zhang, Wenzhi; Li, Dan; Su, Dongming (Frontiers in Surgery, 2025)
PurposeThis study aimed to determine the incidence of bleeding after core needle biopsy (CNB) of infected cervical lymph nodes and analyze the factors associated with bleeding after CNB, and preventive measures of bleeding.MethodsWe retrospectively analyzed the records of 643 patients with infectious cervical lymphatic ganglionic diseases who underwent CNB at our hospital from December 2015 to February 2022. The number of patients with bleeding after CNB, extent of bleeding, and type of disease were recorded and statistically analyzed.ResultsA total of 643 patients with cervical lymph node infection were included in this study. The postoperative and intraoperative bleeding rate of CNB was 23.48% (150/643). Internal lymph node bleeding was most commonly reported (94.0%, 141/150). Lymph nodes containing pus had a higher risk of bleeding than solid lymph nodes (χ²: 12.00, P: 0.001). Lymph node tuberculosis had a significantly higher risk of bleeding than lymph node infection with common bacteria (χ²: 4.10, P: 0.04).ConclusionFollowing CNB, patients with cervical lymph node infection primarily reported internal lymph node bleeding. Lymph nodes with an internal pus cavity surrounded by blood-rich granulation tissue showed a higher risk of bleeding than solid lymph nodes, with heterogeneous enhancement on preoperative contrast-enhanced ultrasound.